A Self-Healing Polymer with Fast Elastic Recovery upon Stretching - Pei-Chen Zhao; Wen Li; Wei Huang; Cheng-Hui Li (Molecules, 2020)
The design of polymers that exhibit both good elasticity and self-healing properties is a highly challenging task. In spite of this, the literature reports highly stretchable self-healing polymers, but most of them exhibit slow elastic recovery behavior, i.e., they can only recover to their original length upon relaxation for a long time after stretching. Herein, a self-healing polymer with a fast elastic recovery property is demonstrated. We used 4-[tris(4-formylphenyl)methyl]benzaldehyde (TFPM) as a tetratopic linker to crosslink a poly(dimethylsiloxane) backbone, and obtained a self-healing polymer with high stretchability and fast elastic recovery upon stretching. The strain at break of the as-prepared polymer is observed at about 1400%. The polymer can immediately recover to its original length after being stretched. The damaged sample can be healed at room temperature with a healing efficiency up to 93% within 1 h. Such a polymer can be used for various applications, such as functioning as substrates or matrixes in soft actuators, electronic skins, biochips, and biosensors with prolonged lifetimes.